Antibacterial and modulatory activities of β-cyclodextrin complexed with (+)-β-citronellol against multidrug-resistant strains. (July 2021) - Silva Pereira, Raimundo Luiz; Campina, Fábia Ferreira; Costa, Maria do Socorro; Pereira da Cruz, Rafael; Sampaio de Freitas, Thiago; Lucas dos Santos, Antonia Thassya; Cruz, Beatriz Gonçalves; Maciel de Sena Júnior, Diniz; Campos Lima, Igor Kleber; Xavier, Maria Regivânia; Rodrigues Teixeira, Alexandre Magno; Alencar de Menezes, Irwin Rose; et al.
Abstract: The present study aimed to investigate the antibacterial and modulatory activities of (+)-β-citronellol (βCT), β-cyclodextrin (β-CD), and their complex βCT/β-CD and characterize them using infrared spectroscopy. Infrared spectra were recorded in the 750–4000 cm −1 region. The antibacterial effects of these compounds and their modulatory-antibiotic activities were determined using the minimum inhibitory concentration (MIC) test. Signatures of these pure compounds were detected in the infrared spectrum of the βCT/β-CD complex. The MIC of the βCT/β-CD complex against the tested strains was found to be 1024 μg/mL. The antagonistic and synergistic effects of these compounds were also observed using the modulation tests. βCT or β-CD alone did not exhibit any direct antibacterial activity. However, the βCT/β-CD complex in combination with gentamicin showed a synergistic effect against E. coli . Highlights: The β-CD/βCT complex and pure β-CD did not possess direct antibacterial activity. The β-CD/βCT complex and pure β-CD, WHEN associated with antibiotics displayed synergistic effects. The β-CD/βCT complex in association with gentamicin showed a synergistic effect against E. coli.